Stress Distribution in Four Restorative Methods in Endodontically Treated Maxillary Premolar: A 3D Finite Element Analysis - Alireza Daneshkazemi; Mohammad Mehdi Jalili Bahabad; Rahele Mirseifinejad; Mohammad Hosein Amirzade Iranaq; elnaz karimian (Mashhad University of Medical Sciences, 2019)
Introduction: the Restoration of endodontically treated teeth is critical, and the Awareness of stresses developed by oblique and vertical forces in restorative methods take a great role in treatment plans. Due to the anatomical shape and inherent form of the stress distribution premolars, could be lost by fractures. Some fractures such as vertical fracture which is probable in endodontically treated teeth, makes the teeth a candidate for extraction and other surgical procedures. According to this fact that the dental restorations should be conservative, the aim of this study was to determine stress distribution using four composite restorative methods. Methods: Endodontically treated maxillary second premolars were restored with composite resin using four methods. For restoration, the models representing standard Mesio-occlusal-distal (MOD) restoration, cusps capping with thickness of 1 and 2mm, and the use of woven fiber in occlusal part, were prepared. The effects of the different restorative approaches on stress distribution were analyzed using three-dimensional finite element stress analysis. Results: the highest stress rate was observed in MOD tooth restoration and the amount of stress in natural parts of the tooth in woven fiber was found the lowest. Conclusion: The simulation results show that in all models, oblique forces caused more stress than vertical forces. Moreover, there was a slight difference between different types of restorations regarding the magnitude of stress; however, the results obtained from this study showed that woven fiber could partly reduce stresses.